Implementation of a clinical decision support tool to improve the adequate prescription of low-molecular-weight heparins in non-surgical patients - Froucke van Gosliga; Dagmar Pals; Annette van Ojik; Eric van Roon (PLoS ONE, 2026)
Background Non-surgical hospitalized patients have an increased risk of developing venous thromboembolism (VTE). This risk can be reduced by thromboprophylaxis with low-molecular-weight heparins (LMWHs), but adherence to thromboprophylaxis guidelines is generally low. Objectives To study the effect of implementing a clinical decision support (CDS) tool in the electronic health record on the percentage of adequately prescribed thromboprophylaxis with an LMWH in non-surgical patients at high risk for VTE. Methods Data on the Padua Prediction Score (PPS) and thromboprophylaxis in high-risk non-surgical patients (≥18 years) were collected at different time points before and after the implementation of the intervention consisting of a validated CDS tool. The percentage of adequately prescribed LMWH thromboprophylaxis was described pre- and post-intervention in a stepwise approach, in which both crude and adjusted pre- and post-intervention differences were assessed using an interrupted time series analysis, accounting for potential time trends and autocorrelation. Results In 400 patients included, 200 pre- and 200 post-intervention, the percentage of adequately prescribed LMWH thromboprophylaxis increased from 78% to 91%, an increase of 13% (95% CI: 6%−20%). This effect diminished to 8% (95% CI: −4%−19%) after adjustment for the pre-intervention slope and autocorrelation. Conclusion In our study, the already high percentage of patients with adequately prescribed LMWH-thromboprophylaxis could potentially be increased further with the implementation of a CDS tool. With increasing amounts of data available in electronic health records, CDS tools might be an efficient and sustainable intervention to improve healthcare quality.